Preaching and Humanity: A Special Reference to the Indian Community in Malaysia - Mohd Yunus, Ahmad Redzuwan (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: There are an effort of dessiminating the message of Islam among the Indian Muslim in Malaysia. This attempts have been performed by Malay and Indian Muslim themselves. However, there is no clear involvement of the government activities of preaching to this community, particularly in assisting some Indian Muslim organisations. Apart from PERKIM, who purposely established for uplifting the welfare of newconverts, it is noted that no massive effort attempted by the government in order to solve many problems among this community. Until now, there are no serious effort to discuss the problem of Indian Muslims in the national level initiated by the government. In fact, the cooperation between non-government preaching organisation are loose pertaining to this matter. Nevertheless, such activities which were practiced by these group would at least maintan the slow but continuous process of preaching among Indian community in the country. One may also predict that there might be several preaching organisations would emerge to lead the India community into Islam if they are able to maintain and upgred their activities from time to time.KEY WORDS: preaching, humanity, government and non-government preaching organisation, and Indian Muslim in Malaysia.About the Author: Assoc. Prof. Dr. Ahmad Redzuwan Mohd Yunus is a Lecturer at the Department of Dakwah and Leadership Study, Faculty of Islamic Study UKM (National University of Malaysia), 43600 Bangi, Selangor Darul Ehsan, Malaysia. He can be reached at: dzuwan@ukm.myHow to cite this article? Mohd Yunus, Ahmad Redzuwan. (2010). âPreaching and Humanity: A Special Reference to the Indian Community in Malaysiaâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.201-210. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 23, 2010); Revised (March 29, 2010); and Published (April 28, 2010).